2007
DOI: 10.1007/s00453-007-9111-9
|View full text |Cite
|
Sign up to set email alerts
|

Generating Cut Conjunctions in Graphs and Related Problems

Abstract: Let G = (V , E) be an undirected graph, and let B ⊆ V × V be a collection of vertex pairs. We give an incremental polynomial time algorithm to generate all minimal edge sets X ⊆ E such that every pair (s, t) ∈ B of vertices is disconnected in (V , E X), generalizing well-known efficient algorithms for generating all minimal s-t cuts, for a given pair s, t of vertices. We also present an incremental polynomial time algorithm for generating all minimal subsets X ⊆ E such that no (s, t) ∈ B is This research was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The idea of our algorithms is as follows. Our algorithms are based on the supergraph technique, which is frequently used in designing efficient enumeration algorithms [4,8,15,16,19,25]. In this technique, we define a directed graph on the set of all solutions and the enumeration algorithm simply traverses this directed graph from an arbitrary solution.…”
Section: • • •mentioning
confidence: 99%
“…The idea of our algorithms is as follows. Our algorithms are based on the supergraph technique, which is frequently used in designing efficient enumeration algorithms [4,8,15,16,19,25]. In this technique, we define a directed graph on the set of all solutions and the enumeration algorithm simply traverses this directed graph from an arbitrary solution.…”
Section: • • •mentioning
confidence: 99%
“…Enumerating the cutsets between all pairs of nodes reduces to the problem of solving a system of linear equations [19]. The notion of cutset has been generalized to cut conjunctions in [17].…”
Section: Related Workmentioning
confidence: 99%
“…In particular, if an enumeration algorithm runs in time that is polynomial in the size of the input graph plus the number of enumerated objects, then it is called output polynomial. A large amount of results have been dedicated to output polynomial enumeration algorithms, e.g., [1,2,[10][11][12]18,[24][25][26]28,[32][33][34], and for various enumeration problems it has been shown that no output polynomial time algorithm can exist unless P = NP [24,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the supergraph technique for enumerating vertex subsets in graphs [2,23,25,32,34], Golovach et al [15] presented a flipping method to generate the out-neighbors of a node of the supergraph, i.e., to generate new minimal dominating sets from a parent dominating set. Using this flipping method they were able to give output polynomial algorithms for enumerating the minimal dominating sets of line graphs and graphs of large girth.…”
Section: Introductionmentioning
confidence: 99%